Best Practices in Central Bank Organizational Culture, Learning and Structure: The Case of the Moroccan Central Bank. (11th August 2015) - Momani, Bessma; St. Amand, Samantha
<x xml:space="preserve">Abstract</x> This paper provides both theoretical and empirical evidence that maintains that a central bank's organizational structure, culture and learning system are important for achieving best governance practices in emerging market economies. It argues that a central bank's organizational structure and culture facilitate the effective implementation of governance practices that have been enacted by law or in a strategic plan, with specific reference to central bank independence, communication, transparency, professionalization, technical excellence and reputation risk management. Qualitative interviews and a review of the bank's primary documents showed that the progress made by the Bank al‐Maghrib over the last two decades in establishing best governance practices in policies and legal statutes is, to a significant extent, being matched by reforms to its internal processes, but there remains room for improvement.